The Effectiveness of The Implementation of Project-Based Learning (PJBL) to Improve Critical Thinking Abilities on Students' Learning Interest in The PPKN Subject - Felia Mutiara Sari; Marzuki Marzuki; Yayuk Hidayah (FKIP - Universitas Riau, 2026)
In 21st century learning, students are expected to develop critical thinking skills, active participation, collaboration, and learning interest through meaningful classroom activities. However, PPKn learning is often still dominated by conventional methods that make students less active in expressing ideas and solving problems. This study aimed to analyse the effectiveness of Project Based Learning (PjBL) in improving students’ critical thinking skills and learning interest in Pancasila and Civics Education (PPKn). This research employed a qualitative case study design involving 30 Grade XI students. Data were collected through classroom observation, interviews, a student questionnaire, and documentation of learning activities and project products. The data were analysed descriptively by identifying patterns of students’ communication, collaboration, motivation, participation, and critical thinking during the implementation of PjBL. The findings show that PjBL encouraged students to become more active in discussing ideas, sharing roles, solving problems, and presenting project results. Students also showed stronger learning motivation because the project produced a concrete cultural miniature related to the PPKn material. This study concludes that PjBL can be used as an alternative learning strategy to strengthen students’ critical thinking skills and learning interest in PPKn learning.